The dilemma of COVID-19 in dental practice concerning the role of saliva in transmission: a brief review of current evidence - Shahram Hamedani; Nima Farshidfar; Ava Ziaei; Hamidreza Pakravan (European Oral Research)
From December 12, 2019, a pandemic of acute respiratory syndrome, the novel human coronavirus disease (COVID-19), caused by a novel β-coronavirus (2019- nCoV) began to grow globally by person-to-person transmission. The production of airborne material during aerosol generating dental procedures would expose dental team and patients to remarkable risk of transmission concerning the faceto-face communication and splattered saliva, blood, and other body fluids. Dental professionals can be a substantial help in preventing the transmission of COVID-19. This study has reviewed relevant current evidences in literature that has addressed the role of saliva and the threats that may be inherent in transmission of the disease during dental procedures. The study also offers feasible proactive and preventive measures for dental practice during the outbreak to block possible person-toperson or indirect transmission in dental settings.